Dielectric and Electrical Properties of LaGaO3 Ceramics - Das, Piyushranjan; Mekap, Anita; Choudhary, R. N. P. (JOURNAL OF ADVANCES IN PHYSICS, 2013)
LaGaO3 based perovskite oxides doped with Sr and Mg exhibit high ionic conductivity over a wide range of oxygen partial pressure and found to be very stable in reducing, oxidizing, and CO2 atmospheres. In this study, the polycrystalline sample of LaGaO3 was prepared by a high-temperature solid-state reaction technique. Preliminary X-ray diffraction (XRD) studies of powder sample of LaGaO3 showed the formation of single-phase compound at room temperature. The surface morphology of the pellet sample of LaGaO3 was recorded at room temperature using a scanning electron microscope (SEM). Detailed studies of dielectric properties (Îµr, tan Î´) and impedance parameters of the material provide an insight into the electrical properties and understanding of types of relaxation process occurred in the material. Temperature variation of dc conductivity shows that this compound exhibits negative temperature coefficient of resistance (NTCR) and frequency dependence of ac conductivity suggests that the material obeys Jonschera’s universal power law.